Analisis Pemanfaatan Media Sosial dalam Strategi Pemasaran Digital terhadap Peningkatan Penjualan Susu Sapi - Muhammad Arsil Adhim; Alyana Mevia Zahra; Atika Rahmanah; Bayu Widodo (Global Leadership Organizational Research in Management, 2025)
In today's digital era, marketing through social media is becoming an increasingly popular strategy in increasing product sales. The use of digital marketing in dairy products can be through online platforms, websites and marketplaces. The purpose of writing this article is to see the effect of implementing social media digital marketing strategies on increasing cow's milk sales. This article uses a literature study research method sourced from national and international journals of previous research results. The results of the journal search found as many as 10 national journals and 5 international journals that meet the criteria set by the author. Based on the results of the review, it can be concluded that some dairy businesses have used social media (Instagram, Facebook, WhatsApp, etc.), but many have not utilized it as a means of product promotion and marketing. However, some businesses that have done marketing through social media, show that social media has a positive impact on increasing sales, brand awareness, and brand trust & loyalty, and effectively expanding consumer reach.